Synthesis and biological evaluation of pyrimidine nucleosides fused with 3 ',4 '-tetrahydrofuran ring - Chun, MW; Kim, MJ; Kim, HO; Moon, HR; Kim, HD; Kim, JH; Jeong, LS (MARCEL DEKKER INC, 2003)
Pyrimidine nucleosides fused with 3,4'-tetrahydrofuran ring were synthesized, starting from 1,2;5,6-di-O-isopropylidene-D-glucose and assayed for antiviral activities. Thymine analogue 1 and its corresponding 2'-deoxy analogue 3 exhibited high cytotoxicity instead of giving antiviral activities.